Implementasi Pendidikan Karakter dalam Digitalisasi Pendidikan - Ma'rufah, Afni (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2022)
This study aims to describe character education in the digitalization of education. Another objective of this research is to formulate character education activities that are suitable to be integrated into the implementation of blended learning and distance learning. The research method used is library research (Library Research). The data collection technique applied in this discussion is to study books, research journals, literature, and other documents deemed relevant to the research problem. The findings in the data collection process are documented for later analysis and presented descriptively. The results of this study are; 1) a study on character education, 2) a study on the application of digitalization of education, and 3) a description of the implementation of character education in the application of digitalization of education.